Effects of institutional characteristics on the performance of climate change adaptation projects in Kenya - Murungi, Violet; Ntongai, David; Huka, Guyo Sarr; Mworia, Eric (African Journal of Science, Technology and Social Sciences, 2025)
Climate change poses a major threat to Kenya’s socioeconomic development, particularly in sectors like agriculture. Consequently, a number of climate change adaptation projects have been implemented across the country. However, these efforts have not shown results of community impact. The objective of this study was to establish the effect of institutional characteristics on the performance of climate change adaptation projects in Kenya. Both quantitative and qualitative methods were used to analyse data. The target population was climate change adaptation projects in Marsabit and Isiolo counties, Kenya, with a total of 2,021 target population. Using Slovin’s Formula, a sample of 334 respondents was derived. Data collection tools included interviews with key informants, questionnaires for beneficiaries, and field observations. Data was analysed using SPSS and Microsoft Excel. A positive correlation was found between stakeholder participation and project performance (correlation = 0.531, p=0.000). The regression analysis indicated a statistically significant effect (F = 97.929, p = 0.000) with a coefficient B1=.199, which suggests that institutional characteristics positively influence project performance. The study concludes that sound institutional characteristics are a critical factor in enhancing the performance of climate change adaptation projects. It recommends the cultivation of transformative leadership styles, the adoption of project implementation structures with a clear flow of command, and the use of communication technology in the implementation of the projects.